Incidence, Clinicopathological Profile and Location - Based Outcome of Intracranial Meningiomas: 10-Year Institutional Study with Review of Literature - Feroze Ganai; Humam Nisar Tanki; Afaq Sherwani; Kirmani Altaf; Nazish Chisti; Altaf Ramzan (Indian Journal of Neurosurgery)
Intracranial meningiomas are the most common extra-axial tumors, representing 15% of all brain tumors. Arising from the arachnoid cells, and common in middle-aged women, 90% meningiomas are benign. We conducted a 10-year study on 183 cases of intracranial meningiomas and observed a lower and decreasing trend; the mean age was 43.3 years but there was also a significant incidence in young females. Parasagittal/falx (29%), sphenoid ridge, convexity meningiomas and middle cranial fossa locations were more common. Histopathologically, meningothelial meningioma was the most common. Benign (WHO I) tumors were found in above 90%, atypical (WHO II) in 5% cases, and malignant (WHO III) in < 4% patients. Most patients underwent Simpsons Grade I excision (35.6%) with dural reconstruction because of late presentations. Posterior fossa meningiomas were mostly benign, while intraventricular ones were mostly malignant with highest postoperation mortality. Mortality in operated patients was 9.8% but was highest in anterior fossa tumors (12.5%).